2016
DOI: 10.1073/pnas.1607151113
|View full text |Cite
|
Sign up to set email alerts
|

Combining natural language processing and network analysis to examine how advocacy organizations stimulate conversation on social media

Abstract: Social media sites are rapidly becoming one of the most important forums for public deliberation about advocacy issues. However, social scientists have not explained why some advocacy organizations produce social media messages that inspire far-ranging conversation among social media users, whereas the vast majority of them receive little or no attention. I argue that advocacy organizations are more likely to inspire comments from new social media audiences if they create "cultural bridges," or produce message… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
94
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 15 publications
1
94
0
1
Order By: Relevance
“…Hence, we use some excellent studies as reference for validating our approach. From a methodological point of view, we are in line with Bail (2016). In such a work, the author presents remarkable results in the social field combining text mining and network analysis to study how advocacy organizations stimulate conversation on social media.…”
Section: Recent Contributions Likesupporting
confidence: 54%
See 1 more Smart Citation
“…Hence, we use some excellent studies as reference for validating our approach. From a methodological point of view, we are in line with Bail (2016). In such a work, the author presents remarkable results in the social field combining text mining and network analysis to study how advocacy organizations stimulate conversation on social media.…”
Section: Recent Contributions Likesupporting
confidence: 54%
“…In such a work, the author presents remarkable results in the social field combining text mining and network analysis to study how advocacy organizations stimulate conversation on social media. Despite the differences in objectives pursued, our research and Bail (2016) share the utilization of the frequencies of the words to measure text similarity. Then, both studies involve the usage of communities detection algorithms to capture clusters in the data.…”
Section: Recent Contributions Likementioning
confidence: 99%
“…It is here where the computer sciences can be especially helpful, offering innovative ways to examine social and political problems [43][44][45][46][47][48][49]. And, as larger amounts of digitized observational and historical data are made available, researchers will do well to consider the ways that computational approaches like natural language processing or unsupervised learning might unlock new methods for conducting research on seemingly impenetrable and opaque issues like misinformation and philanthropy.…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that 'climate denial'challenges to the overwhelming scientific consensus around climate change-has been effectively utilized by the so-called climate countermovement as a means to block political progress [2, 9-11, see also 12]. In particular, this research has focused on the diffusion of disinformation to the public by organizations that received corporate funding.At the same time, scholars have taken advantage of innovations in computational social science to provide insights into 'exactly how connections among people create societal trends' [2,[13][14][15]. Employing computational research methods, this paper looks at how climate denial has become a central organizing force in climate politics under the Trump Administration.…”
mentioning
confidence: 99%
“…At the same time, scholars have taken advantage of innovations in computational social science to provide insights into 'exactly how connections among people create societal trends' [2,[13][14][15]. Employing computational research methods, this paper looks at how climate denial has become a central organizing force in climate politics under the Trump Administration.…”
mentioning
confidence: 99%